Who are the bad guys and what do they want? - Fell, Gregory J., 1964-; Barlow, Mike (Michael Alan) (O'Reilly Media, 2016)
Recent breaches at the Internal Revenue Service are a stark reminder that cyber crime is alive and well. According to Center for Strategic and International Studies, cyber crime and cyber espionage cost the global economy between $375 billion and $575 billion annually, or roughly 1% of global income. So who are those guys and what do they want? Based on interviews with several cyber security experts, this O'Reilly report provides a concise and highly informative look into various actors who populate this murky world. You'll explore some of their methods and motivations, as well as new approaches from the both US government and private sector to help organizations manage cyber security more aggressively. The threat from international criminals, state-sponsored hackers, terrorists, mischievous students, and even coworkers is continuing unabated. Get a copy of this report and find out what your organization can do to deal with this ongoing threat.